An experimental analysis using taguchi method in resolving the significant factors subject to corrosion under insulation - Burhani, N.R.A. (Asian Research Publishing Network, 2016)
Corrosion under insulation (CUI) is a gradually vital issue for piping in industries especially petrochemical and chemical plants due to its astonishing catastrophic disaster and automatic impact on the environmental problem. To ensure this CUI problem does not spark sudden surprise in plants, indeterminate factors that contribute to the deterioration of CUI should be recognized and taken care seriously. Thus, this research will unearth the most influential factors for the CUI deterioration using Taguchi method for design of the experiment. Result analysed using a signal to noise ratio revealed that most significant factor for CUI occurrence is insulation type followed by service temperature. However, this method also exposes that interactions between factors for CUI are less significant. Meanwhile, the most influential factor for service temperature is 120oC, type of insulation are perlite and calcium silicate while cycle type is isothermal wet/dry. This will help as an acceptable guideline for inspection planning purpose and priority in the maintenance schedule. Â©2006-2016 Asian Research Publishing Network (ARPN).